La transmutation identitaire au service de l’émancipation ethnoculturelle et de la revitalisation linguistique en Catalogne du Nord - Maria Antón i Álvarez de Cienfuegos (Lengas)
This paper represents a substantial theoretical contribution to academic discussions on the management and negotiation of individual identity within minority ethnocultural communities. The introduced concept, termed 'identity transmutation,' delineates the process of identity construction elicited by revelatory experiences and unfolds across three stages: crisis, self-discovery, and commitment. This identity transmutation significantly influences the individual reappropriation of ethnocultural symbols within the minority community and contributes to the social revitalization of minority language and culture. The study is grounded in 39 in-depth qualitative interviews, presenting a compelling collection of autobiographical narratives. The selected participants span different generations and originate from Northern Catalonia, a distinctive sociolinguistic setting within France.